2014
DOI: 10.1016/j.nbt.2014.05.945
|View full text |Cite
|
Sign up to set email alerts
|

MAR elements and transposons for improved transgene integration and expression

Abstract: Reliable and long-term expression of transgenes remain significant challenges for gene therapy and biotechnology applications, especially when antibiotic selection procedures are not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Matrix attachment regions can increase expression levels of the transgene in stably transfected CHO cells [6][7][8][9][10][11][12]. However, the characteristics and mechanism of MARs function have not been elucidated, and further studies are needed to develop improved methods for transgene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Matrix attachment regions can increase expression levels of the transgene in stably transfected CHO cells [6][7][8][9][10][11][12]. However, the characteristics and mechanism of MARs function have not been elucidated, and further studies are needed to develop improved methods for transgene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Scaffold/matrix attachment regions (S/MARs) can block transgene silencing [6][7][8] and increase transgene expression levels and stability in host cells [9][10][11][12][13][14][15]. In addition, S/MARs can also reduce variations in transgene expression among different cells to some extent, and the rate of transgene genomic integration can be increased [11]. However, some reports have shown that S/MARs have inconsistent effects on transgene expression [16][17][18].…”
mentioning
confidence: 99%
“…There are two types of vectors: integrated and non-integrated vectors. Integrated vectors facilitate the insertion of mutations, and may be responsible for diseases arising as a result of the position of the inserted gene (Buceta et al, 2011;Ley et al, 2013). Ideal non-integrated vectors present no potential risk in gene therapy, are stable through mitosis, and express high levels of the transgene (Girod et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The use of the MAR, developed in recent years, can effectively overcome exogenous gene inactivation. Many studies have focused on increasing the expression of exogenous genes using nuclear MARs (Klehr et al, 1991;Chavali et al, 2011;Harraghy et al, 2011;Jin et al, 2012;Koirala et al, 2013;Ley et al, 2013). MAR sequences may increase the production of recombinant proteins (Harraghy et al, 2012), and β-globin MAR can improve the stable genomic expression of the Sleeping Beauty transposon (Sjeklocha et al, 2011).…”
Section: Discussionmentioning
confidence: 99%